2022
DOI: 10.3390/brainsci12010101
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time to Test the Antiseizure Potential of Palmitoylethanolamide in Human Studies? A Systematic Review of Preclinical Evidence

Abstract: Antiseizure medications are the cornerstone pharmacotherapy for epilepsy. They are not devoid of side effects. In search for better-tolerated antiseizure agents, cannabinoid compounds and other N-acylethanolamines not directly binding cannabinoid receptors have drawn significant attention. Among these, palmitoylethanolamide (PEA) has shown neuroprotective, anti-inflammatory, and analgesic properties. All studies examining PEA’s role in epilepsy and acute seizures were systematically reviewed. Preclinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, growing evidence indicates a crucial role for neuroinflammation in neurodegeneration ( 8 ) and a potential therapeutic effect of neuroinflammation modulation in contrasting neurodegeneration at both the neurobiological and behavioral level ( 11 ). In this regard, recent research highlights the importance that cannabinoid-related compounds, whose actions depend on the interaction with non-CB receptors, may have in terms of anti-inflammatory properties ( 16 18 ), in turn accounting for their ability to mitigate biological mechanisms involved in neurodevelopmental disorders ( 53 ), epilepsy ( 15 ), and neurodegeneration ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, growing evidence indicates a crucial role for neuroinflammation in neurodegeneration ( 8 ) and a potential therapeutic effect of neuroinflammation modulation in contrasting neurodegeneration at both the neurobiological and behavioral level ( 11 ). In this regard, recent research highlights the importance that cannabinoid-related compounds, whose actions depend on the interaction with non-CB receptors, may have in terms of anti-inflammatory properties ( 16 18 ), in turn accounting for their ability to mitigate biological mechanisms involved in neurodevelopmental disorders ( 53 ), epilepsy ( 15 ), and neurodegeneration ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, NCDs represent the group of conditions where the use of PEA seems to be the most supported by research studies, with an overwhelming convergence of evidence toward a therapeutic effect on core cognitive symptoms and underlying neurobiological underpinnings. Also, compared to other conditions, such as autism spectrum disorders ( 53 ) or epilepsy ( 15 ), where the evidence for a therapeutic potential of PEA is robust, but very limited ( 53 ) or absent ( 15 ) in humans, the present review identified 7 studies performed in humans. Such studies were either in vivo, in vitro , or observational studies, and a preliminary meta-analysis of studies assessing cognition before and after PEA administration ( 24 , 27 , 28 ) revealed an effect of PEA in partially reversing cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the FDA has approved purified cannabidiol (CBD), nabiximols, dronabinol, and nabilone with indications for treatment in very specific neuropsychiatric conditions [ 32 ]. In parallel, great interest has been aroused regarding the therapeutic potential of terpenoids and endocannabinoid-like compounds [ 33 , 34 ].…”
Section: Raising Concern About Cannabis Exposure In Autism Spectrum D...mentioning
confidence: 99%